A Conceptual Model of Hybrid Monitoring Rehabilitation Progress of Stroke Patients: A Case Study of a Public Tertiary Hospital in Malaysia - Ismail, W; Zamin, N; Hanafi, MH; Mohamad, AH (IEEE, 2024)
Rehabilitation in healthcare systems provides therapy and training to restore quality life after certain illness, addiction or accident. Currently, there is a significant unmet need for rehabilitation services, and it is frequently undervalued in the health system. As populations age and the prevalence of noncommunicable diseases and injuries increases, and the demand for rehabilitation grows, strengthening rehabilitation in health systems becomes ever more paramount. Conventional rehabilitation service can be costly and time consuming to people not living near the rehabilitation centres. Often people with lower income who live in rural areas refuse rehabilitation services due to the logistic issue. On the other hand, in urban areas, most people are too busy with their daily activities and unable to keep their therapy schedule consistently. In consequence, patients do not enjoy the actual benefit of rehabilitation because of a certain limitation such as cost and time. These limitations can be surpassed by putting telerehabilitation, an emerging area of performing rehabilitation medical treatment with the use of technology from a distance into practice. Scientific studies of telerehabilitation in the current literature are discussing primarily in the area of readiness, technologies, and illnesses such as children autism and heart failure. However, there is limited evidence about telerehabilitation service for stroke patients, concentrating on the pre-implementation and implementation stages, which makes this paper viable and significant, potentially for telerehabilitation implementation in Malaysia. This paper proposes a new conceptual model of hybrid telerehabilitation that combines several technological principles, such as cloud, virtual reality, and computer-based system. The model was derived based on a study of a public tertiary hospital in Malaysia. The current traditional system was investigated and discussed. A new telerehabilitation model is proposed to widen the access for rehabilitation to patients of all ages.